PENEGAKAN HUKUM YANG TIDAK BERSESUAIAN DENGAN KETENTUAN HUKUM PIDANA DALAM PROSES PENYELIDIKAN DAN PENYIDIKAN YANG MENYEBABKAN TIMBULNYA KORBAN (Dalam Kajian Ilmu Viktimologi) - Julaiddin Julaiddin (UNES Journal of Swara Justisia, 2018)
In the law has been discussed about the investigation of Law No. 8 of 1981 on the Criminal Procedure Code (KUHAP) as the basis of the footing process at the level of investigation. For that, a truly real process is needed to find errors that may not cause the mistrust caused by the process. Thus the legal process can be upgraded to an investigation to determine the primary and can be found by the real culprit.